Pre-scaling up of Improved Maize Technology in the Lowland and Moisture Stress Areas, Borena Zone, Southern Oromia, Ethiopia - Kassa, Teshome; Desiso, Feyissa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Today, maize grows from moisture-stress areas to high rainfall areas and vice versa. The purpose of this study was to improve the productivity, local capacity and linkage among relevant stakeholders. The study was conducted in Yabello district, selected purposively based on the convenience and potentiality of maize production. A total of 18 trial farmers selected purposively. A land size of 0.25ha was used at each site of the trial farmers. All agronomic practices applied. Both quantitative and qualitative data were generated and analyzed using descriptive statistics and narration, respectively. The result revealed that the mean yield of Melkassa-1 was significant (p<0.05) across production years. High demand observed and therefore, it was recommended for further promotion until alternative variety released.